Planning for Improvement of Carton Box Production Process using Lean Manufacturing Approach to Increase Production Results at PT. Kati Kartika Murni - Raihanah Yusuf; Sumiharni Batubara (JURNAL TEKNIK INDUSTRI, 2019)
Abstract—PT. Kati Kartika Murni is a company engaged in the packaging industry. This company applies a make to order (MTO) system. Carton Boxes are the focus of research because it have the highest number of requests by 55%. Problems faced by PT. Kati Kartika Murni namely the number of customer requests not yet met. This research was conducted to increase the production of carton boxes to 3600 boxes. Increasing the amount of production is done by lean manufacturing approach, namely by identifying waste and eliminating existing waste. Manufacturing lead time before repair is 17811.7 seconds, process cycle efficiency before repair is 44.4489%, and takt time is 4.645 seconds. The number of production before the design of repairs is 3379 boxes, where orders have not been fulfilled with the available time. The highest waste based on the waste assessment model and value stream analysis tools are defect and transportation. The analysis was conducted using the Failure Mode and Effect Analysis (FMEA) method to determine the type of waste that needs to be eliminated. The highest RPN of 448 is the faded color defect in the flexo process and the second highest RPN of 392 is the overlap defect in the corrugating process. Waste transportation analysis using FMEA method shows the highest RPN value of 448, namely at the time of operation and material movement on the production floor. The design of improvements to eliminate waste transportation is to add a roller conveyor functioning as material handling between work stations. One piece flow addition for the corrugating process to flexo. After an improvement plan is made, the Manufacturing lead time is 15634.2 seconds and the Process cycle efficiency is 50.64%. The amount of production after the design improvement is 3850 boxes, where orders have been fulfilled with the available time.